Could building replacements significantly contribute to seismic vulnerability mitigation at urban scale? Case studies of two typical swiss cities - Lestuzzi, Pierino (Frontiers in Built Environment, 2022)
This paper contains an investigation on the potential decrease of seismic vulnerability related to building replacements for the cities of Sion and Martigny in Switzerland. Those two cities were identified for the present research based on the accuracy of the corresponding available information. Seismic assessment at urban scale was recently achieved for both cities and new buildings are systematically indexed according to the construction regulation of the canton of Wallis (Valais). Sion and Martigny belong to the largest cities of the canton of Wallis and this region is characterized by the highest seismicity within Switzerland. The investigation focuses on a 4-year period between 2016 and 2019. Cases for which an existing building is demolished and replaced by a new one were identified and checked. Those cases do not represent general practice. The majority of new buildings are built on free land. Consequently, the building replacement rate is too low to lead to a significant decrease of the seismic vulnerability at urban scale. In addition to the systematic appropriate seismic design of new buildings, retrofitting of existing buildings therefore remains the adequate strategy for seismic vulnerability mitigation. In case of replacement, low-rise buildings are generally replaced by mid-rise buildings. Moreover, unreinforced masonry buildings are usually replaced by reinforced concrete shear-wall buildings. This slightly impacts the building stock distributions but the seismic vulnerability is not significantly changed, since the demolished buildings are not the most vulnerable ones. Nevertheless, few obvious isolated vulnerability decreases occurred with respect to the demolition of soft-story buildings for instance. By contrast, seismic vulnerability may also be increased in the case where a new building is built against an existing one with a different story level and without an adequate seismic separation joint.